Kultuurrade vir 'n demokratiese Suid-Afrika: historiese oorsig oor die konstitutionalisering en institusionalisering van kultuurbelange in 'n plurale samelewing - Kriek, D. J. (Faculty of Humanities, University of the Free State, 2009)
The South African Constitution provides for the establishment of cultural councils in the country. This article traces the origin of the concept in South Africa and how it developed since it was first proposed round about the mid-seventies of the previous century. Contributions by individuals, commissions of enquiry, political parties, government departments, the KwaZulu-Natal Indaba, the Constitutional Assembly and even the example of the Belgian political system are all investigated and evaluated. To a large extent the article is based on the proposals and contributions made by the author in this regard as well as on the prospects for a future dispensation in which cultural councils for various groups could balance and support one another for the sake of maintaining unity and diversity in society and the state.
Keywords: Constitutionalization; Institutionalization; South African Constitution; Cultural counsils; Government departments; Commissions of enquiry; Political parties